Uso de duas espécies de macrófitas aquáticas, Eichhornia crassipes e Pistia stratiotes em tratamento de resíduos de cervejaria na cidade de Toledo/PR - Sales, Cristina Viana (2011)
The accumulation and deposition of high concentrations of organic matter cause the eutrophication of aquatic environments, and a sustainable alternative to the removal of these compounds is phytoremediation. This study evaluated the potential of two floating aquatic macrophytes, Eichhornia crassipes and Pistia stratiotes in the treatment of brewery wastewater. The treatment system consisted of eight experimental units, and the experimental design 2 treatments and 4 pseudoréplicas, each treatment was coupled to a mechanical filter in closed circulation system. We analyzed the parameters temperature, electrical conductivity, pH, dissolved oxygen, turbidity, COD, total phosphorus, nitrogen, nitrite and nitrate, and measure the biomass of macrophytes, the experiment lasted 21 days, with collections made weekly. Statistical analysis showed no statistical difference between treatments for the reduction of nutrients, however the two species E. crassipes and P. statiotes been proven effective in removing these nutrients. As for weight gain, E. crassipes had a higher growth compared to P. stratiotes. The use of phytoremediation is recommended for the treatment of brewery effluents due to low cost, easy maintenance and efficiency of aquatic macrophytes in removing nutrients that cause eutrophication of aquatic environments.